Efforts to Improve the Quality of Packaging and Labeling of Spice Products at CV. XYZ - Jariyah; Reni Dwi Anggraini (Future Science, 2023)
Businesses in the food sector are the most popular business sector in Indonesia. As the largest spice-producing country in the world, this is the background to which this business is starting to emerge because it has quite large growth prospects. CV. XYZ exploits this potential by creating ready-to-use spice products that are claimed to have functional properties for cooking mixtures. Mandi seasoning and lemon & pepper seasoning are products that are being developed by CV. XYZ has been packaged in kilos of plastic and plastic spice bottles but has not been labeled by applicable regulations. This service aims to help partners improve packaging and labeling to improve product quality by government regulations. The implementation method used is approach, the introduction of labels and packaging, direction, and assistance activities in making label designs. The results achieved are more attractive and informative packaging labels, the introduction a marketable type of packaging by using additional aluminum foil packaging in the standing pouch model as a packaging variation, and increased consumer confidence and the competitiveness of similar products on the market.